Application of Building Shame Culture at University Students - Purba, Nelvitia (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is a distortion carried out by humans by manipulating truth and honesty and contradicting religious values, human values and society. Corruption eradication programs carried out by the judiciary and law enforcement agencies such as the Corruption Eradication Commission (KPK) need to be supported by the Indonesian people. One of the programs against corrupt practices such as bribery, embezzlement, theft and waste of state money is to increase the culture of shame in preventing corrupt practices.This research uses the theory of public linkages with the 'Malay communication' approach which aims to offer cognitive concepts as well as applicative in building a culture of shame for the prevention of corrupt practices among students. The method used in this paper is (a) literature review: books relating to local wisdom of Malay culture, Malay character education, and (b) writings and other books relevant to the modeling of 'culture of shame preventing corruption.'Based on the results of this study, it can be concluded (1) The practice of abuse of formal authority that occurs in government agencies leads to the inability to understand and apply textual messages of Malay heritage which has long been a fencing of social and national law, (2) Comprehension of message items to invite and appealed to the community to build a sense of shame has not been fully implemented because of the sense of not being involved and not interested in participating in public spaces.